Description of Comorbid Diseases in Outpatients on Hemodialysis at Hospital X, Kediri Region 2024 - Putri, Elsa Mahardika; Lukitasari, Dhunik; Mawarni, Okky Intan; Dhafin, Anis Akhwan (Contemporary Journal of Applied Sciences, 2024)
Background.Chronic kidney disease is a global public health problem with increasing prevalence and incidence of chronic kidney failure, poor prognosis and high costs (Ministry of Health of the Republic of Indonesia, 2017). Chronic kidney disease is a progressive condition that affects more than 10% of the general population worldwide or more than 800 million people (National Kidney Foundation, 2021). The results of the 2018 Basic Health Research (Riskesdas) showed that the prevalence of chronic kidney disease in the population over 15 years of age in Indonesia in 2013-2018 was 3.8% and in Central Java Province it was 4%, higher than the national prevalence rate. Purpose. of this study was to determine the description of comorbidities in hemodialysis outpatients at Hospital X in the Kediri area. Method.This research method uses a quantitative non-experimental analytical descriptive design. Sampling was conducted using the Purposive Sampling technique and obtained a sample of 52 hemodialysis patients at Hospital X. Results.The results of the study showed that the majority were male (55.77%), the highest age range was 55-64 years (50%), the highest duration of hemodialysis was 1-5 years (55.77%), the highest type of comorbidity was hypertension and the majority of the number of comorbidities was one disease. Conclusion The conclusion of this study is expected to provide a picture of comorbidities in hemodialysis outpatients, so that comprehensive nursing care can be carried out to minimize complications and improve the quality of life of hemodialysis outpatients.